Preparation and Photocatalytic and Antibacterial Activities of Micro/Nanostructured TiO2-Based Photocatalysts for Application in Orthopedic Implants - Qi, Liang; Guo, Binghua; Lu, Qing; Gong, Hanghui; Wang, Min; He, Jinlong; Jia, Bin; Ren, Jing; Zheng, Shicheng; Lu, Yufeng (Frontiers in Materials, 2022)
Micro/nanostructured TiO2, ion-doped TiO2, and heterojunction TiO2 composite photocatalysts have low toxicity, high biocompatibility, and high photocatalytic and antibacterial activities and have broad applications in the fields of photocatalytic, antibacterial, and orthopedic implants. The photocatalytic and antibacterial activities of TiO2 and TiO2-based photocatalysts depend on their preparation methods. In this review, the preparation methods of TiO2, ion-doped TiO2, and heterojunction TiO2 composite photocatalysts and their effects on photocatalytic and antibacterial activities were reviewed. Based on the excellent physical and chemical properties of TiO2, ion-doped TiO2, and heterojunction TiO2-based photocatalysts, their applications in the field of orthopedic implants were reviewed. Meanwhile, the development trend of the photocatalyst in the fields of photocatalysis, bacteriostasis, and medicine was prospected. The purpose of this review was to point out the direction for further study on photocatalytic and antibacterial activities and related applications of TiO2 and TiO2-based photocatalysts.